Unraveling drivers and patterns of species richness in coastal marine ecosystem under global warming: Insights from ecosystem connectivity - Xiangyan Yang; Jia Wo; Toniann Keiling; Yong Chen (Ecological Indicators)
Both climatic and anthropogenic drivers influence marine ecosystem richness patterns in various ways. In coastal ecosystems, estuarine inputs and the availability of estuarine habitats significantly affect species richness by shaping species distribution and population productivity. The varying responses of different species to changing environmental conditions also contribute to the dynamics of richness patterns. To comprehensively understand the temporal and spatial patterns of species richness, it is essential to consider multiple drivers and species-level dynamics. This study developed a framework that integrates key drivers of species richness dynamics based on the interconnections between different ecosystem components. We applied this framework to the Hudson River Estuary-New York Bight (HRE-NYB) ecosystem to elucidate how warming temperature, fishery pressures, primary production variation, zooplankton community dynamics and estuary habitat availability shape richness trends and patterns of NYB through ecosystem interconnection during the study period (1980–2022). Regime shift and correlation analyses suggest that environmental pressures are the primary stressors driving changes in HRE-NYB fish and macroinvertebrate richness, rather than fishing pressure. Using center of gravity and species-level dynamics analysis, we identified different temporal and spatial responses to warming temperature across estuary and marine habitats and between lower and higher trophic levels. Environmental and ecological linkages between HRE and NYB habitats within and across seasons, coupled with warming temperatures, contribute to increased species richness in the NYB. Seasonal patterns in the NYB richness was influenced by thermal conditions and species migration. In the context of the U.S. Northeast Continental Shelf Large Marine Ecosystem (NES), we found that richness indicators in the NYB reflect influences from both southern and northern ecoregions. We recommend utilizing finer temporal and spatial scales in ecosystem assessments and recognizing the NYB as a crucial sentinel for detecting regime shifts in the NES ecosystem.